Case report : Subclinical verminous pneumonia and high ambient temperatures had severe impact on the anesthesia of semi-domesticated Eurasian tundra reindeer (Rangifer tarandus tarandus) with medetomidine-ketamine - Tryland, Morten; Josefsen, Terje D.; Sanchez Romano, Javier; Marcin, Nina; Mørk, Torill; Arnemo, Jon Martin (Frontiers in Veterinary Science, 2021)
publishedVersion